Avaliação ultraestrutural dos processos de granulogênese e secreção e do perfil mitocondrial durante a diferenciação e ativação de eosinófilos - Kennedy Bonjour de Oliveira Ferreira (2019)
Eosinophil, an innate immune cell, plays an important role in both health and disease through its remarkable secretory capacity. Along their development, eosinophils pre- synthesize dozens of proteins and store in secretory granules called specific granules. Cytokines such as, Stem Cell Factor (SCF) and Interleukin-5 (IL-5) are involved in eosinophil differentiation. However, little is known about the process of eosinophil granulogenesis, and the action of SCF under these cells. In the present work, conventional transmission electron microscopy (MET) or electron tomography techniques were applied to investigate the processes of granulogenesis and secretion and mitochondrial profile during eosinophil differentiation and activation. Thus, bone marrow cells were collected from mice to establish an ex vivo eosinophil culture system. Differentiating eosinophils were evaluated at different stages of culture (0, 4, 8, 10, 12 and 14 days) while mature eosinophils were stimulated with SCF, eotaxin-1 (CCL11) or tumor necrosis factor-alpha (TNF- α). In parallel, human eosinophils isolated from blood and stimulated in vitro with SCF and tissue eosinophils under the effect of in situ SCF treatment were investigated by MET to identify their secretory processes. Only 12% of the cells had mature granules on day 14 of culture. With SCF supplementation, a 100% of the mature eosinophil population was achieved. During differentiation of murine eosinophils, the specific granules undergo condensation and crystallization processes, which lead to the mature form, characterized by the presence of crystalloid granules. 3D studies revealed for the first time the presence of intragranular membranes forming tubular structures during the condensation process of specific granules, which demonstrates the structural complexity of these organelles. In parallel, murine eosinophil mitochondria reduce along cell matures and release vesicles from the outer membrane. In the presence of inflammatory agonists, mitochondria undergo swelling and loss of cristaes. When directly stimulated with SCF, mature murine eosinophils were able to secrete IL-6, but not IL-4 or IL-13. SCF-stimulated human eosinophils degranulate by piecemeal (vesicular transport of their products) or cytolysis (cell death with deposition of granules in tissues). In addition, they release tubular vesicles (Sombrero vesicles - EoSVs) from free granules in the extracellular medium, indicating an unrecognized vesiculatios ability. Our data demonstrate that both specific granules and mitochondrial profile of eosinophils undergo dynamic processes throughout cell maturation and can respond to cellular activation with morphological changes.